The Relationship between Accurate Use of Antibiotics and Clinical Improvement of Sepsis in Neonates Using the Gyssens Method in the Perinatology Ward of Dr. M. Djamil General Hospital, Padang Indonesia - Freidlander Pangestu; Rinang Mariko; Didik Hariyanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Neonatal sepsis is a major cause of neonatal morbidity and mortality in developing countries. Inappropriate use of antibiotics causes an increase in antibiotic resistance, so the Gyssens method is needed, which is a qualitative method and is used to evaluate the use of antibiotics. This study aims to determine the relationship between the accuracy of the use of antibiotics using the Gyssens method on the clinical improvement of neonates in the Perinatology Ward of Dr. M. Djamil General Hospital Padang, Indonesia. Methods: This study used a cross-sectional conducted from January 2020 to December 2020. The study subjects were 67 neonates diagnosed with sepsis in the perinatology ward of Dr. M. Djamil General Hospital, Padang Indonesia. Data analysis was performed with SPSS for univariate and bivariate analysis. Results: Most neonatal sepsis occurs in male infants who have low birth weight. Most cultures do not grow. There was an improvement in clinical and hematological parameters to the administration of first-line, second-line, and culture-appropriate antibiotics according to the Gyssens method, but statistically not significant (p-value > 0.05). The rational use of antibiotics was 89.6%. Conclusion: There is a relationship between the accuracy of antibiotic use on clinical improvement and blood parameters of neonatal sepsis patients in the Perinatology ward of Dr. M. Djamil General Hospital based on the Gyssens method, but it is not statistically significant. The use of antibiotics based on the Gyssens method at Dr. M. Djamil General Hospital is quite good.